2000
DOI: 10.1097/00006254-200009000-00016
|View full text |Cite
|
Sign up to set email alerts
|

Paget’s Disease of the Vulva: Pathology, Pattern of Involvement, and Prognosis

Abstract: Gynecol Oncol 2000;77:183–89 This is a retrospective review of 76 patients with Paget's disease of the vulva from the MD Anderson Cancer Center. The authors also divided patients into four groups by diagnosis, the majority (46) being intraepithelial Paget's disease. Nine patients had invasive Paget's disease; an additional 13 patients had intraepithelial Paget's disease with another coexisting cancer. Coexisting cancers of interest included endometrial, ovarian, breast, and cervical carcinomas. The mean age of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
75
1
4

Year Published

2002
2002
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(81 citation statements)
references
References 0 publications
1
75
1
4
Order By: Relevance
“…Furthermore, the majority of studies have focused on vulvar Paget's disease. 2,4,[13][14][15][16][17] We analysed the prognostic factors of EMPD arising in both genders using 76 patients treated at two neighbouring institutions. In our series, male patients outnumbered female patients (male : female ratio, 2AE6 : 1), in contrast to previous reports.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the majority of studies have focused on vulvar Paget's disease. 2,4,[13][14][15][16][17] We analysed the prognostic factors of EMPD arising in both genders using 76 patients treated at two neighbouring institutions. In our series, male patients outnumbered female patients (male : female ratio, 2AE6 : 1), in contrast to previous reports.…”
Section: Discussionmentioning
confidence: 99%
“…Compared with patients with carcinoma in situ (CIS), patients with malignancies underlying dermis and subcutaneous tissues or lymph node metastasis appear much worse prognosis. 5,6 Therefore, in the treatment of extramammary Paget's disease, indications of lymph node dissection are an important issue as well as wide local excision (WLE).…”
mentioning
confidence: 99%
“…EMPD frequently occurs during the sixth decade of life. 1 In our study, the mean age was 66.6 years, with the youngest case of 47 years old. 2,4 It was reported that EMPD was common in females, the ratio of male to female was from 1: 1 to 1:4.…”
Section: Discussionmentioning
confidence: 56%
“…EMPD is histologically characterized by intraepidermal proliferation of Paget's cells similar to classic mammary Paget's disease. 1,2 EMPD was reported to be associated with certain visceral malignancies, such as carcinomas of bladder, colon, kidney and prostate; however, the exact relationship between EMPD and other malignancies remains unclear. In addition, 18-60% recurrence of EMPD was reported in patients with invasive lesions whereas no such local recurrence was observed in patients with epidermal EMPD lesions.…”
mentioning
confidence: 99%